Produção de mudas de rúcula utilizando substrato de resíduos orgânicos do restaurante universitário e de poda de grama da UTFPR - câmpus Campo Mourão - Nunes, Flaviane Galvani (2018)
Composting propitiate a useful destination for organic compounds, avoidinng to acummulate in embankments. This process results in the organic compound that can be applied to the soil to improve its characteristics, without causing risks to the environment. The efficiency of the composting process is directly related to factors that provide optimum conditions for aerobic microorganisms to multiplying and acting in the transformation of organic matter. The set of conditioning factors for the good development of a biologically complex system such as composting should be marked by a series of parameters, and each type of material to be composted requires an optimal combination of humidity, aeration, C / N, pH and granulometry. The objective of this study was to evaluate the use of organic compost obtained from residues at the university restaurant and UTFPR - Campo Mourão, in the production of arugula seedlings, comparing it with a commercial substrate. It were collected combings of compounds and pruning compounds to mount compost pile. Then the assembly was carried out and the process was monitored. At the end of the composting experiment, physical-chemical analyzes and agronomic viability evaluation were performed on arugula. To evaluate the growth of the plants the agronomic growth variables were: mean plant height, leaf number, fresh and dry matter mass of plants. The organic and commercial compounds presented values close to the analyzed parameters. There was a significant difference in all variables analyzed. The organic compound presented better results to the commercial substrate, indicating the viability of its use in the cultivation of arugula.